Can Psychosocial Intervention Suppress Testosterone and Triglycerides Among Women With Polycystic Ovary Syndrome? A Feasibility Trial - Yin, Margaret X. C.; Du, L. B.; Zou, X. N.; Fung, Y. L.; Sun, Y. Y.; Chan, Celia H. Y.; Chan, Cecilia L. W. (Frontiers in Psychology, 2021)
Women with polycystic ovary syndrome (PCOS) suffer significant psychological distress, which may activate the hypothalamus-pituitary-ovary axis and further affect their physiological state. They often experience elevated levels of testosterone and triglycerides. Considering reports of psychological distress among women with PCOS, this study aimed to develop a psychosocial intervention to improve their emotional and physical health, particularly in Chinese society. This pilot study employed the Integrative Body-Mind-Spirit (I-BMS) intervention model for women with PCOS in China. After a two-hour health information session, 18 participants were randomly assigned to the I-BMS group (9) or the control group (9). The intervention group received six weekly, three-hour I-BMS sessions. Pre- and post- blood tests and psychosocial questionnaires were collected from all participants. Retention to treatment was high with 79.6% treatment adherence gained and an overall average of five sessions completed. Compared with the control group, depression and anxiety symptoms reduced significantly for those in the intervention group (d=-1.24, p<0.05 and d=-1.33, p<0.01), their health-related quality of life improved significantly (d=1.02, p<0.01) both at post-intervention and three-month follow-up, and their testosterone and triglycerides levels reduced significantly (d=-0.97, p<0.001 and d=-0.41, p<0.05) after joining the intervention. The I-BMS model is feasible and appears promising in improving psychological health, and reducing testosterone and triglyceride levels, in women with PCOS in China. This trial was registered at www.chictr.org.cn (registration number ChiCTR1900027606).